2016
DOI: 10.1186/s12936-016-1610-1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing insecticide resistance in Anopheles funestus and Anopheles arabiensis in Malawi, 2011–2015

Abstract: BackgroundSusceptibility of principal Anopheles malaria vectors to common insecticides was monitored over a 5-year period across Malawi to inform and guide the national malaria control programme.MethodsAdult blood-fed Anopheles spp. and larvae were collected from multiple sites in sixteen districts across the country between 2011 and 2015. First generation (F1) progeny aged 2–5 days old were tested for susceptibility, using standard WHO procedures, against pyrethroids (permethrin and deltamethrin), carbamates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 42 publications
3
57
0
Order By: Relevance
“…Phenotypic and molecular evidence have demonstrated that pyrethroid resistance in An. funestus in Malawi is largely driven by oxidase enzymes that contribute to metabolic detoxification of pyrethroids [41,42]. In settings of moderate intensity of monooxygenase-based resistance, such as Malawi, the WHO recommends the deployment of ITNs with the synergist piperonyl-butoxide (PBO) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic and molecular evidence have demonstrated that pyrethroid resistance in An. funestus in Malawi is largely driven by oxidase enzymes that contribute to metabolic detoxification of pyrethroids [41,42]. In settings of moderate intensity of monooxygenase-based resistance, such as Malawi, the WHO recommends the deployment of ITNs with the synergist piperonyl-butoxide (PBO) [43].…”
Section: Discussionmentioning
confidence: 99%
“…1 Mean and range of values: haemoglobin (Hb gl -1 ); haematocrit (%); Thr = thrombocytes (×10 3 ml -1 ); creat = creatinine (mg ml -1 ); bil = total bilirubin (mg ml -1 ); Glasgow score (Glas); % of parasitized erythrocytes (%pE); CM = cerebral malaria; MM = mild malaria; n.s. 4 Percentage of individuals with positive blood smear at recruitment. 2 Percentage of males.…”
Section: Clinic and Biological Characteristics Of The Cohort Of Malarmentioning
confidence: 99%
“…3 Percentage of individuals who declared treatment before hospitalization. 4 Percentage of individuals with positive blood smear at recruitment. 5 Comparison of biological results (Mann-Whitney test).…”
Section: Clinic and Biological Characteristics Of The Cohort Of Malarmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrethroids, along with other pesticides, are also widely used to control agricultural pests on livestock and field crops worldwide [3]. The past decade has seen a dramatic increase in reports of physiological pyrethroid resistance in malaria vectors [4][5][6][7][8][9][10][11][12][13][14][15]. The rapid increase in pyrethroid resistance necessitates an immediate proactive resistance management response to avoid compromising existing effective interventions.…”
Section: Introductionmentioning
confidence: 99%